Growth and flowering inhibition of Paspalum notatum with application of trinexapac-ethyl and prohexadione-calcium - Marchi, Sidnei R. de; Martins, Dagoberto [UNESP]; Costa, Neumarcio V. (Univ Federal Campina Grande, 2016)
This study aimed to evaluate the effect of sequential applications of plant regulators on growth and seedhead emergence of Bahiagrass (Paspalum notatum). The study was carried out on a 15-month-old lawn, in a randomized block design, with four replicates. The treatments consisted of the following plant-growth regulators and dose: trinexapacethyl in sequential application of 113 + 113, 226 + 113, 226 + 226, 452 + 113, 452 + 226, 452 + 452 g a.i. ha(-1); trinexapac-ethyl in single application of 678 and 904 g a.i. ha(-1); and prohexadione-calcium in sequential application of 100 + 100 and 200 + 200 g a.i. ha(-1), besides a control, with no application. The effects of treatments were evaluated based on visual injury, plant height, height and number of flower rachises and total dry matter production of clippings. Sequential applications of prohexadione-calcium at 100 + 100 or 200 + 200 g a.i. ha(-1) were efficient to reduce plant height, but did not show efficacy to reduce the number and height of seedheads or the total dry matter of clippings of Bahiagrass. However, Bahiagrass lawns can be managed by trinexapac-ethyl sequential applications of 452 + 452 g a.i. ha(-1) or single application of 904 g a.i. ha(-1), with reduction in the need for mowing for a period of up to 113 days after application, without causing any deleterious effect on the visual aspect of the lawn.
Keywords: Bahiagrass; growth inhibitors; sequential application